2022
DOI: 10.1177/03331024221082506
|View full text |Cite
|
Sign up to set email alerts
|

Cervical musculoskeletal impairments in the 4 phases of the migraine cycle in episodic migraine patients

Abstract: Objective To assess cervical musculoskeletal impairments during the 4 phases of a migraine cycle in episodic migraine patients, controlling for the presence of concomitant neck pain. Methods Differences in cervical musculoskeletal impairments were assessed during the 4 migraine phases in episodic migraine patients and compared with healthy controls controlling for concomitant neck pain. Cervical musculoskeletal impairments were assessed as follow: cervical active range of motion; flexion rotation test; cranioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 101 publications
0
18
0
Order By: Relevance
“…Statistically, the two most common differential diagnoses for MSK HA are the most common primary HA types: TTH and migraine. Additionally, some pieces of evidence support the upper neck involvement in the clinical presentations of both TTH (42, 57, 58) and migraine (8,59). Interestingly, in migraine, cervical MSK findings may be real or apparent due to hypersensitivity which may lead to subjective neck complaints without objective neck impairments (6,60,61) and, therefore, should be carefully checked.…”
Section: Screening and Classifying Ha/ofp In The Msk Practice: The Tr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Statistically, the two most common differential diagnoses for MSK HA are the most common primary HA types: TTH and migraine. Additionally, some pieces of evidence support the upper neck involvement in the clinical presentations of both TTH (42, 57, 58) and migraine (8,59). Interestingly, in migraine, cervical MSK findings may be real or apparent due to hypersensitivity which may lead to subjective neck complaints without objective neck impairments (6,60,61) and, therefore, should be carefully checked.…”
Section: Screening and Classifying Ha/ofp In The Msk Practice: The Tr...mentioning
confidence: 99%
“…Due to the convergence of sensory input from the upper cervical spine and the trigeminal nerve into the trigeminocervical nucleus of the brainstem, nociception from both the upper neck and the masticatory system has the potential to play a role in the neurophysiology of primary HA ( Figure 1 ) ( 4 , 5 ). However, although patients with migraine are very likely to complain about neck pain, it is shown that their cervical spine is not necessarily objectively impaired ( 6 8 ). Since primary HAs lack specific underlying pathology, they are considered a pain disorder, and as such, management approaches are multi-disciplinary and include among other treatment modalities, physiotherapy with some evidence to support it ( 9 ).…”
Section: Headache and Orofacial Pain In The Musculoskeletal Practicementioning
confidence: 99%
“…Excessive force, repetitive motion, bad posture or extended stationary position, and vibration are among the activities that might cause neck discomfort issues. 14,15 The fourth most common cause of disability, neck discomfort, has a yearly prevalence rate of above 30%. 16 Whether the pain is mechanical or neuropathic can be determined by the history and physical examination.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Liang et al (2021) suggested that the presence of neck pain in persons with migraine does not necessarily indicate altered cervical function, as 61% of the migraine cohort assessed had similar cervical musculoskeletal function than healthy controls. On the other hand, Di Antonio et al (2022) reported that in all phases of the migraine cycle, independent of the presence of concomitant neck pain, episodic migraine patients showed altered cervical function, demonstrated by the reduced flexion rotation test and craniocervical flexion test and an increased number of myofascial trigger points and positive test for the passive accessory vertebral segments. However, the cervical range of motion and cervical pressure pain threshold were altered only in the ictal phase.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Di Antonio et al. (2022) reported that in all phases of the migraine cycle, independent of the presence of concomitant neck pain, episodic migraine patients showed altered cervical function, demonstrated by the reduced flexion rotation test and craniocervical flexion test and an increased number of myofascial trigger points and positive test for the passive accessory vertebral segments. However, the cervical range of motion and cervical pressure pain threshold were altered only in the ictal phase.…”
Section: Introductionmentioning
confidence: 99%